Efek Latihan Beban Metode Circuit Training terhadap Peningkatan Ukuran Otot pada Mahasiswa Tidak Terlatih - Harun, Harun; Hadi, Rokhman; Wardiyanto, Yayan (Institut Teknologi Bandung, 2023)
Increasing muscle mass or hypertrophy is becoming a popular goal in fitness center. The circuit training method has the potential to be an alternative method to increase muscle mass because it can perform various exercises in a short time. this study aims to determine the effect of circuit training on increasing muscle mass in Sports Science students of the University of Muhammadiyah Cirebon. This study used an experimental method using a pre-test post-test design control group. Twensty male college students with an average age of 21±1.78 years old and an average body weight of 73.68±17.56 kg were divided into two groups, namely the treatment class and the control class. The treatment class is given a circuit training training method while the control class uses a traditional mothoed (multiset method). Treatment is done for 4 weeks the frequency of exercise 2-3 times per week. Body circumference (arm circumference, chest circumference, thigh circumference) are measured by measuring tape, muscle percentage and body fat percentage are measured by BIA (Bioelectrical Impedence Analysis) brand Omron type HBF-375. Data analysis using paired sample t test and independent sample t test. Based on the results of using an independent sample t test, it was found that the treatment class experienced significantly better values compared to the control class with a signification value of arm circumference of 0.013 and a thigh circumference value of 0.002 (p < 0.05). In muscle percentage, the treatment class was better than the control class with a significance value is 0.002 (p<0.05) The circuit training method was significantly better on arm circumference and thigh circumference parameters as well as muscle percentage than the traditional unprogrammed method.